2019
DOI: 10.3892/or.2019.7193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cofilin‑1 and Twist‑1 protein expression in human non‑small cell lung cancer tissues

Abstract: Metastasis is the primary cause of mortality in patients with non-small cell lung cancer (NSCLC). Actin cytoskeletal reorganization is usually accompanied by the epithelial-mesenchymal transition (EMT)-induced invasion and metastasis of cancer cells. In the present study, expression levels of the actin-associated protein cofilin-1 and of the pivotal EMT molecule Twist-1 were determined in NSCLC tissues. Using lung cancer tissue arrays, the identification of 67.4% of tissue spots that exhibited reciprocal level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Previous studies about CFL1 had focused on autoimmune diseases, T-cell differentiation, Alzheimer's disease, and tumorigenesis among the biological function of CFL1 (8, 17-19). The CFL1 expression was higher in pancreatic cancer, NSCLC, hepatocellular carcinoma, and esophageal squamous cell carcinoma (7,12,13,20,21). In epithelial ovarian cancer cells, phosphorylation of Co lin-1 enhances Paclitaxel resistance by preventing the apoptosis of cancer cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies about CFL1 had focused on autoimmune diseases, T-cell differentiation, Alzheimer's disease, and tumorigenesis among the biological function of CFL1 (8, 17-19). The CFL1 expression was higher in pancreatic cancer, NSCLC, hepatocellular carcinoma, and esophageal squamous cell carcinoma (7,12,13,20,21). In epithelial ovarian cancer cells, phosphorylation of Co lin-1 enhances Paclitaxel resistance by preventing the apoptosis of cancer cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…CFL1 is an actin‐binding protein that is involved in various processes of cell invasion and metastasis, and plays an important role in epithelial mesenchymal transition (EMT) and cytoskeletal reorganization 24,25 . It has been shown that CFL1 plays an important role in regulating the invasion, metastasis, prognosis and drug resistance of lung cancer 26–28 . Inhibition of CFL1 activity can reduce the movement of tumor cells, which is a potential target for suppressing the growth and spread of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 It has been shown that CFL1 plays an important role in regulating the invasion, metastasis, prognosis and drug resistance of lung cancer. [26][27][28] Inhibition of CFL1 activity can reduce the movement of tumor cells, which is a potential target for suppressing the growth and spread of tumors.…”
mentioning
confidence: 99%